2015
DOI: 10.1139/apnm-2014-0242
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the removal of chocolate milk from school milk programs for children in Saskatoon, Canada

Abstract: Studies in the United States report inclusion of flavoured milk in the diets of children and youth improves nutrient intakes. No research has investigated the contribution of flavoured milk to overall milk intake or the milk preferences of Canadian children. The objective of the study was to measure milk consumption (plain milk and flavoured milk) by children in an elementary school environment and investigate factors contributing to milk choice. A mixed-method research design was applied across 6 schools for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 17 publications
(20 reference statements)
3
29
1
1
Order By: Relevance
“…This may be due to reasons such as the close proximity to rural farm land and the strong agricultural influence on the city, both of which can increase milk consumption. 34,50 Racial or ethnic breakdown was not measured in this study, so the specific demographics of the subjects are unknown. In general, Guelph is a relatively fast growing, rural-influenced, prosperous city in southern Ontario.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to reasons such as the close proximity to rural farm land and the strong agricultural influence on the city, both of which can increase milk consumption. 34,50 Racial or ethnic breakdown was not measured in this study, so the specific demographics of the subjects are unknown. In general, Guelph is a relatively fast growing, rural-influenced, prosperous city in southern Ontario.…”
Section: Discussionmentioning
confidence: 99%
“…12,32,33 The total consumption of milk could decrease as much as 48% with no adaptation to drinking plain milk. 13 Moreover, it would be important to elucidate the difference in effects on total milk consumption over varying time periods to see whether the drops are permanent or if children become accustomed to drinking plain milk. One study found a substantial reduction in milk consumption following complete elimination of flavored milk from schools in a shorttime period.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Previous studies have shown that children who drank flavored milk consumed more total milk overall compared with children who consumed white milk [4][5][6] and there was significantly less wastage of milk. 12,13 Despite the nutritional benefits flavored milk has in the diets of children, some school districts are removing flavored milk from the lunchrooms. What has fueled the debate is that chocolate milk can contain up to twice as much sugar as white milk and as a result may contribute to total energy and added sugars intake.…”
mentioning
confidence: 99%
“…The importance of flavor in foods cannot be overemphasized. For instance, a study in Canada found that when chocolate‐flavored milk was not an option, many children were not drinking milk . The flavor of food could be natural or artificial.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a study in Canada found that when chocolate-flavored milk was not an option, many children were not drinking milk. 21 The flavor of food could be natural or artificial. Artificial flavorings are mostly used in beverages to impart a flavor of choice, to modify an already existing flavor, or as a way of masking some undesirable flavor.…”
Section: Resultsmentioning
confidence: 99%